Wise Ancestors and Current Social Issues as Guides to the Design of Contemporary Programs of Teacher Education. (2nd January 2020) - Berliner, David C.
ABSTRACT: I slowly developed the belief that sharing much of educational research with novice teachers was an error. To me, novice teachers appeared to have too little experience to adopt and adapt research to particular school sites and classrooms. I urge, therefore, that more of an apprenticeship in classroom life, and greater understanding of the families and the community served by a school, precede attempts to implement research findings. Moreover, since so many of the outcomes of education are dependent on the quality of life lived by the children and families in the school community, I urge teacher educators to infuse their programs with training in political activity appropriate for teachers. Better lives for the families and children in their charge should be an educators' first goal. If that can be accomplished, achievement in school subjects is more likely to follow.